Modeling the impact of climate change on suitable areas for the underutilized crop Cyperus esculentus (tiger nut) and implications for production expansion and conservation in Togo, West Africa - Koffi Kibalou Palanga; Anissou Bawa; Jacques Idohou Kadjogbé Ayena; Dowo Michée Adjacou; Thierry Dèhouégnon Houehanou; Gérard Nounagnon Gouwakinnou; Armand Kuyema Natta (Discover Agriculture)
Abstract Cyperus esculentus L., an important food and medicinal plant, is increasingly threatened by climate change in Togo. This study aims to model its current and future distribution using the MaxEnt and Bioclim algorithms, incorporating environmental variables and occurrence data from the field and the GBIF database. Projections were made using three climate scenarios (SSP1-2.6, SSP2-4.5, SSP5-8.5) for the time horizon 2041–2060. The results show that soil, altitude, minimum temperature of the coldest month, annual precipitation and agricultural production strongly influence the distribution of the species. Both models perform well (AUC, TSS, SEDI), but MaxEnt is superior. Currently, 40% of the country is suitable for tiger nut cultivation, with optimal habitats concentrated in the south. Future scenarios predict a strong decrease of suitable areas in the north and a slight expansion towards the center and south. Bioclim expects more significant losses, especially under SSP5-8.5. The overlap of current producer villages with future habitats shows that they would all be located in unsuitable areas by 2050. Priority conservation areas covering 35 to 66% of the territory have been identified but remain poorly represented in protected areas. These results highlight the need to rethink tiger nut management policies in Togo, focusing actions on introducing the crop in newly suitable areas, supporting affected producers, and integrating the identified priority areas into national climate change adaptation strategies.